A Load-Sharing Rip-Stop Fixation Construct for Arthroscopic Rotator Cuff Repair - Patrick J. Denard, M.D.; Stephen S. Burkhart, M.D. (Arthroscopy Techniques, 2012)
Despite advancements in arthroscopic rotator cuff repair techniques, achieving tendon-to-bone healing can be difficult in the setting of poor-quality tendon. Moreover, medial tendon tears or tears with lateral tendon loss may preclude standard techniques. Rip-stop suture configurations have been shown to improve load to failure compared with simple or mattress stitch patterns and may be particularly valuable in these settings. The purpose of this report is to describe a technical modification of a rip-stop rotator cuff repair that combines the advantages of a rip-stop suture (by providing resistance to tissue cutout) and a double row of load-sharing suture anchors (minimizing the load per anchor and therefore the load per suture within each anchor).